2017
DOI: 10.1016/j.bjm.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Production of docosahexaenoic acid by Aurantiochytrium sp. ATCC PRA-276

Abstract: The high costs and environmental concerns associated with using marine resources as sources of oils rich in polyunsaturated fatty acids have prompted searches for alternative sources of such oils. Some microorganisms, among them members of the genus Aurantiochytrium, can synthesize large amounts of these biocompounds. However, various parameters that affect the polyunsaturated fatty acids production of these organisms, such as the carbon and nitrogen sources supplied during their cultivation, require further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…This result is also in agreement with the recent studies conducted by Furlan et al . 36 and Chen et al . 37 which concluded that high nitrogen concentration in the cultivation medium inhibited the growth of Aurantiochytrium sp.…”
Section: Resultsmentioning
confidence: 94%
“…This result is also in agreement with the recent studies conducted by Furlan et al . 36 and Chen et al . 37 which concluded that high nitrogen concentration in the cultivation medium inhibited the growth of Aurantiochytrium sp.…”
Section: Resultsmentioning
confidence: 94%
“…In another study, strain Aurantiochytrium sp. ATCC PRA-276 generated 9.3 g/L of cell dry weight when cultivated on 30 g/L of glucose with 3 g/L of total nitrogen (1.36 g/L (NH 4 ) 2 SO 4 , 13.63 g/L yeast extract, and 13.63 g/L monosodium glutamate), whereas a higher cell dry weight was observed when the strain was cultivated on 0.44 g/L of total nitrogen (0.2 g/L (NH 4 ) 2 SO 4 , 2.0 g/L yeast extract, and 2.0 g/L monosodium glutamate) with the same amount of glucose [44]. Other thraustochytrid species such as Schizochytrium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Recent researches have focused on Aurantiochytrium as a sustainable source of PUFAs, such as docosahexaenoic acid [2123]. PUFAs have received great interest because of their health benefits and their widespread use in the food and pharmaceutical industries [24].…”
Section: Discussionmentioning
confidence: 99%